Gender discrimination in workforce and its impact on the employees - Zahid Ali Channar; Zareen Abbassi; Imran Anwar Ujan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
This research paper explores the issue of gender discrimination in workforce and its impact on the satisfaction and motivation, commitment and enthusiasm and stress level of employees. Close ended questionnaire was administered from 526 males and females of lower, middle and higher category employees of public and private health and education departments of Hyderabad and Jamshoro districts. Gender discrimination in workforce was measured through independent samples-t test. The analysis shows that females were discriminated more than males in private organizations. Thus the findings show that females are discriminated more than males in private sector than in public sector. The impact of gender discrimination on satisfaction & motivation, commitment & enthusiasm and stress level was assessed through Pearson product moment correlation co-efficient. The results show that gender discrimination decreases satisfaction & motivation and commitment & enthusiasm level of employees, and increases the stress level in the employees
Keywords: 330; Gender discrimination; Workforce; Satisfaction & Motivation; Commitment & Enthusiasm; Stress Level; Geschlechterdiskriminierung; Arbeitszufriedenheit; Leistungsmotivation; Stress; Arbeitskräfte; Indien